HIV Protease Inhibitors Impact on Apoptosis - Rizza, Stacey A.; Badley, Andrew D. (Medicinal Chemistry, 2008)
HIV protease inhibitors are the backbone of HIV therapy. In addition to blocking intracellular HIV protease and dramatically decreasing viral burden, the protease inhibitors also regulate apoptosis. A growing body of data has confirmed the immunomodulatory effects of HIV protease inhibitors which block CD4+ and CD8+ T cell death in models of HIV infection. The mechanism of this apoptosis inhibition is still under active investigation and supported by several proposed hypothesis for how they alter the fate of the cell. More recently, the anti-apoptotic effects of the HIV protease inhibitors has been extended to the non-HIV, non-immune cell, whereby protease inhibitors prevent apoptosis, and disease, in animal models of sepsis, hepatitis and stroke. Interestingly, when HIV protease inhibitors are used at supra-therapeutic concentrations, they exert pro-apoptotic effects. This has been demonstrated in a number of tumor models. Although it is unclear how HIV protease inhibitors can induce apoptosis at increased concentrations, future research will define the targets of the immunomodulation and reveal the full clinical potential of this intriguing class of drugs.
Keywords: HIV replication